“Sacerdócio feminino”: uma análise da violência simbólica em torno do processo de ordenação pastoral de mulheres na convenção batista paraibana - Farias, Alana Carla Lucena (2021)
The representations of gender over time were built in a complex way and loaded with prejudices and stereotypes. Women were present in reports and historical texts, but not as actives subjects, beying discussed in a generic and stereotyped way. Despite all the evolution and progress, nowadays it can still be perceived women, even in the religious milieu, being debated and limited. When we look at the Brazilian evangelical church, we can see how this trend is repeated, especially when it comes to their active role as leaders of Christian institutions. In this context, in the Brazilian Baptist Convention, as well as in the one from Paraiba, much was discussed until a consensus was established about the pastoral ordination of women. Heated speeches and divided votes marked this process that only confirmed the polarity when the issue involves the female priesthood. Thus, the question that guides the research is: how was the process of accepting Baptist pastors in Paraíba? Based on this assumption, the work aims to analize all the way to the legitimization of the vocations´ministry, paying attention to the personal experience of each pastor within the religion. In addition, it is intended to verify the presence of symbolic violence during this process, as being a subtle and almost invisible form of oppression, working as an ally to male domination. For this, the qualitative nature of the research will be explored to formulate the hypothesis, resorting to document analysis and environmental investigation through the interview of four pastors, chosen for their fundamental role in the process of approval of female ordination.